The Effect of Realistics Mathematics Education Models to Enhancement Students’ Mathematics Solving-Problem Ability - Dianita Karunia Dianita; Ishaq Nuriadin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Teachers still use traditional teaching methods, so students' mathematical problem-solving abilities must improve. Because the anticipated model lends itself to improving students' math problem-solving abilities, the authors of this study applied the Realistic Mathematic Education model. This study aims to ascertain how the Realistic Mathematics Education Model affects students' aptitude for solving mathematical problems. Quasi-experimentation is an adopted research approach. Nonequivalent Control Group Design is the format adopted for design. The participants of this study were all fourth-grade students of SDN Cipadu 1 Tangerang City for the 2022–2023 year. The research uses a saturation sampling strategy. Sixty-one students were included in the sample for this investigation. This study uses verified and considered reliable tools in the form of tests. The aim is to determine how students' ability to solve math problems affects data; the SPSS 22.0 program is used for analysis. The results showed that the significance of the t-test was 0.000, indicating that the Realistic Mathematics education paradigm significantly impacted students' mathematical problem-solving ability.